Evaluating the conservation impact of Antarctica's protected areas - Burrows, Joanna L.; Lee, Jasmine R.; Wilson, Kerrie A. (Conservation Biology, 2023)
Antarctic specially protected areas (ASPAs) are a key regulatory mechanism for protecting Antarctic environmental values. Previous evaluations of the effectiveness of the ASPA system focused on its representativeness and design characteristics, presenting a compelling rationale for its systematic revision. Upgrading the system could increase the representation of values within ASPAs, but representation alone does not guarantee the avoided loss or improvement of those values. Identifying factors that influence the effectiveness of ASPAs would inform the design and management of an ASPA system with the greatest capacity to deliver its intended conservation outcomes. To facilitate evaluations of ASPA effectiveness, we devised a research and policy agenda that includes articulating a theory of change for what outcomes ASPAs generate and how; building evaluation principles into ASPA design and designation processes; employing complementary approaches to evaluate multiple dimensions of effectiveness; and extending evaluation findings to identify and exploit drivers of positive conservation impact. Implementing these approaches will enhance the efficacy of ASPAs as a management tool, potentially leading to improved outcomes for Antarctic natural values in an era of rapid global change. Evaluación del impacto de conservación de las áreas protegidas de la Antártida.